The influence of experimental design on the magnitude of the effect size -peer tutoring for elementary, middle and high school settings: A meta-analysis. (2016) - Zeneli, Mirjan; Thurston, Allen; Roseth, Cary
Highlights: Experimental design influences the magnitude of the effect size for peer tutoring (PT). Instrument type for PT pre-post design influences the magnitude of the effect size. The overall effect size for PT is reported to be small to moderate. Effect sizes were positive for elementary, reciprocal-PT, low socio-economic students. Abstract: A meta-analysis was undertaken on a form of cooperative learning, peer tutoring. The effects of experimental design on outcomes were explored, as measured by Effect Size ( ES ). Forty one articles with 49 studies were included in the meta-analysis. ES were positive for peer tutoring with highest effects in elementary, reciprocal role tutoring conducted with low socio-economic class students with high ethnic minorities. ES was influenced by experimental design including design, matching of population samples at pre-test and selection of attainment measures. The implications for future meta-analyses and educational research design in peer tutoring and more broadly are explored.